2013
DOI: 10.1093/tropej/fms061
|View full text |Cite
|
Sign up to set email alerts
|

Bubble CPAP versus Ventilator CPAP in Preterm Neonates with Early Onset Respiratory Distress--A Randomized Controlled Trial

Abstract: BCPAP has higher success rate than VCPAP for managing preterm neonates with early onset respiratory distress, with comparable safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 22 publications
2
41
0
Order By: Relevance
“…The RSS has been used in other low-income/middleincome hospitals to guide CPAP treatment, 17,20 and our study suggests this is a reliable tool for hospitals lacking blood gas machines or x-ray capability. However, additional follow-up testing of health-care providers is needed to establish long-term retention of reliable RSS assessment skills, and correlation with blood gas measurements is warranted to establish accuracy in detecting respiratory failure.…”
Section: Discussionmentioning
confidence: 73%
“…The RSS has been used in other low-income/middleincome hospitals to guide CPAP treatment, 17,20 and our study suggests this is a reliable tool for hospitals lacking blood gas machines or x-ray capability. However, additional follow-up testing of health-care providers is needed to establish long-term retention of reliable RSS assessment skills, and correlation with blood gas measurements is warranted to establish accuracy in detecting respiratory failure.…”
Section: Discussionmentioning
confidence: 73%
“…Several studies addressed secondary outcomes (reduction in need for mechanical ventilation via an endotracheal tube,37–39 and safety and efficacy of bubble CPAP compared with ventilator-driven CPAP35 40 41), while the largest number were case-series describing practical experience with CPAP, both bubble-based or via other systems 31 32 34 42–48. All studies described the use of CPAP in hospitals, with no studies describing home CPAP.…”
Section: Resultsmentioning
confidence: 99%
“…Martin et al 6 conducted a systematic review of the safety and efficacy of bubble CPAP in neonatal care in low-income and middle-income countries. The majority of studies were case series but they identified four randomised trials, two conducted in India (N=30 and N=114),7 8 one in Iran (N=50)9 and one in South America (N=256) 10. They found no evidence of survival benefit from bubble CPAP in low-income and middle-income countries, but conclude that though the reported studies are limited by poor study design and quality, bubble CPAP appears to be safe and to reduce the need for mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%